Phase I/IIa, open-label, multicentre study to evaluate the optimal dosing and safety of ODM-203 in patients with advanced or metastatic solid tumours. Issue 6 (1st December 2020) - Bono, Petri; Massard, Christophe; Peltola, Katriina J; Azaro, Analía; Italiano, Antoine; Kristeleit, Rebecca S; Curigliano, Giuseppe; Lassen, Ulrik; Arkenau, Hendrik-Tobias; Hakulinen, Pasi; Garratt, Chris; Ikonen, Tarja; et al.
Abstract : Background: Genetic alterations in fibroblast growth factor receptor (FGFR) and vascular endothelial growth factor receptor (VEGFR) signalling are observed in various tumours. We report a first-in-human phase I/IIa trial evaluating tolerability, pharmacokinetics and preliminary antitumour activity of ODM-203, a novel FGFR and VEGFR inhibitor. Methods: Open-label, non-randomised, multicentre, phase I/IIa dose escalation and expansion study in patients with advanced or metastatic solid tumours. Results: Overall, 84 patients received treatment; optimal tablet dose was found to be 400 mg/day with food. All patients experienced at least one adverse event; the majority (89.2%) were grade 1 or 2% and 70.4% were considered treatment related. The most commonly reported events were bilirubin increase-related events (75%) and diarrhoea (50%). Overall response rate was 9.2% and median progression-free survival was 16.1 and 12.4 weeks for patients with aberrant or non-aberrant FGFR tumours. Median time on treatment was 10.1 weeks for all patients and 14.5 weeks for patients who received 400 mg tablets. Conclusion: This study suggests ODM-203 400 mg/day results in sufficient plasma concentrations and acceptable tolerability in most patients. Preliminary signs of therapeutic activity of ODM-203 in patients with solid tumours was observed. Trial registration number: NCT02264418 .